Cyclic behavior of lightly reinforced concrete moment frames with partial- and full-height masonry walls. Issue 2 (May 2020) - Han, Sang Whan; Lee, Chang Seok
Existing lightly reinforced concrete (RC) moment frames are vulnerable to earthquakes. The seismic behavior of these frames could be affected by the presence of masonry infill walls. The objective of this study was to investigate the seismic behavior of gravity-designed RC frames having partial- and full-height masonry infill walls. For this purpose, experimental and numerical studies were conducted. Three one-story and one-bay gravity-designed RC moment frames with and without partial- and full-height masonry infill walls were made and tested under cyclic lateral loads. Numerical models for RC moment frames and masonry walls were proposed based on test data. Nonlinear static and incremental dynamic analyses (IDAs) were conducted for three-story RC moment frames with and without partial- and full-height masonry infill walls using the numerical models. Both experimental and numerical studies demonstrated that the masonry-infilled RC frames had larger lateral strength and stiffness than bare RC frames, whereas their drift capacity was less than that of bare frames. The partial-height masonry-infilled RC model frame had the least collapse strength among the frames.